2022
DOI: 10.1111/avj.13156
|View full text |Cite
|
Sign up to set email alerts
|

The innate immune stimulant Amplimune® is safe to administer to young feedlot cattle

Abstract: Background Infectious disease has a significant impact on livestock production. Availability of alternatives to antibiotics to prevent and treat disease is required to reduce reliance on antibiotics while not impacting animal welfare. Innate immune stimulants, such as mycobacterium cell wall fractions (MCWF), are used as alternatives to antibiotics for the treatment and prevention of infectious disease in a number of species including cattle, horses and dogs. This study aimed to evaluate the safety of Amplimun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The absence of detectable negative effects on the immune responses to vaccination evaluated in the current study and safety data from prior experiments (Alexander et al 2022) support the further evaluation of the benefits of Amplimune in either experimental trials that include a pathogenchallenge component or in a commercial feedlot setting. The inclusion of a pathogen-challenge component to future pen trials would enable the indirect assessment of any benefits of Amplimune on the complete immune response to vaccination, rather than the limited number of immune factors measured in the current study.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…The absence of detectable negative effects on the immune responses to vaccination evaluated in the current study and safety data from prior experiments (Alexander et al 2022) support the further evaluation of the benefits of Amplimune in either experimental trials that include a pathogenchallenge component or in a commercial feedlot setting. The inclusion of a pathogen-challenge component to future pen trials would enable the indirect assessment of any benefits of Amplimune on the complete immune response to vaccination, rather than the limited number of immune factors measured in the current study.…”
Section: Discussionsupporting
confidence: 63%
“…The primary interest in using Amplimune is to potentiate nonspecific immune defences as an alternative to antibiotics for the prevention and/or treatment of microbial diseases, such as BRD, in production animals. In view of its previously noted adjuvant-like activities (Alexander et al 2022), administration of Amplimune might also confer beneficial or detrimental effects on antigen-specific responses of the adaptive immune system to contemporaneous vaccination. In the current study, Amplimune, administered at the same time, but at a different anatomical location, as Bovilis MH + IBR or Rhinogard in yearling beef cattle had no detrimental effect on responses to vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The formulation of aluminium hydroxide, monophosphoryl lipid A, and fungal mannan, delivered subcutaneously, elicited rapid (24 h) and sustained (28 days) innate immune responses that protected mice from bacterial and fungal challenge [ 171 ]. Alexander et al [ 172 ] reported that a similar innate immune system stimulant, Amplimune ® , is safe for use in young beef cattle. Amplimune ® consists of the cell wall fractions of Mycobacterium phlei formulated with squalene.…”
Section: Development Of Mrna Vaccines For Important Livestock Diseasesmentioning
confidence: 99%